L’interprétation présidentialiste de la Constitution bolivienne au cœur de la crise post-électorale de 2019 - Victor Audubert (Cahiers des Amériques Latines)
The post-electoral crisis of 2019 can be seen as a consequence of a certain interpretation of the Bolivian Constitution of 2009. A presidentialist interpretation, based on the continuities of presidential mandates, has prevailed in the understanding and application of constitutional norms, whether through the constitutional judge or the electoral organ. This presidentialist interpretation, by challenging the popular will expressed in the referendum of 2016, has led to a process of deconstitutionalization that may partly explain the institutional crisis that followed the general elections of 20 October 2019 and the de facto presidency of Jeanine Áñez.